2017
DOI: 10.1007/s40265-017-0713-5
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Stability to the Chronic Obstructive Pulmonary Disease Patient: Clinical and Pharmacological Considerations for Frequent Exacerbators

Abstract: Acute exacerbations of chronic obstructive pulmonary disease (AECOPD) are critical events associated with accelerated loss of lung function, increased morbidity, and excess mortality. AECOPD are heterogeneous in nature and this may directly impact clinical decision making, specifically in patients with frequent exacerbations. A “frequent exacerbator” is a sub-phenotype of COPD that is defined as an individual who experiences ≥2 moderate to severe exacerbations per year. This distinct subgroup has higher mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 136 publications
(144 reference statements)
0
7
0
Order By: Relevance
“…However, patients are likely to experience relapse after relief of symptoms; drug resistance, side effects, and other complications have been reported during hospitalization. 20 Jianpi Huatan Tongfu granule is a clinical prescription for the treatment of AECOPD. It has been used in TCM for many years, especially in the context of combined clinical treatment using Chinese and Western medicines, where it effectively alleviates the side effects of Western medicines.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients are likely to experience relapse after relief of symptoms; drug resistance, side effects, and other complications have been reported during hospitalization. 20 Jianpi Huatan Tongfu granule is a clinical prescription for the treatment of AECOPD. It has been used in TCM for many years, especially in the context of combined clinical treatment using Chinese and Western medicines, where it effectively alleviates the side effects of Western medicines.…”
Section: Discussionmentioning
confidence: 99%
“…The goals of care for COPD management include reducing symptoms, improving health status and exercise tolerance, and reducing the risk of COPD exacerbations (periods of acute worsening of symptoms) to ultimately prevent disease progression and reduce mortality [ 1 ]. Acute exacerbations negatively impact health status, accelerate lung function decline, and increase mortality risk [ 1 , 5 ]. Overall, they account for more than half the hospitalizations in COPD [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acute exacerbations negatively impact health status, accelerate lung function decline, and increase mortality risk [ 1 , 5 ]. Overall, they account for more than half the hospitalizations in COPD [ 5 ]. In France, a retrospective study of administrative records between 2007 and 2012 revealed that of 29,779 patients admitted to hospital with a severe exacerbation, over 8% died during hospitalization [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, both the pathology and treatment strategies of AECOPD are diverse [ 6 , 7 ]. The prevalence of viral infection in AECOPD was reported to be 42.7% in a recent trial [ 8 ].…”
Section: Introductionmentioning
confidence: 99%